Kesadaran Hukum Orang Tua tentang Hak-Hak Anak: Faktor Penyebab Anak Bekerja pada Sektor Informal - Orpa J. Nubatonis; Yossie M.Y. Jacob; Chatryen M. Dju Bire (Warmadewa Press, 2023)
Children have a number of rights such as getting an education, playing and socializing, having their primary needs fulfilled. His childhood must be filled with positive and useful activities for the child's life in the future. For example, playing and hanging out, following formal education and non-formal education. Thus, the child will become a human being with the ideal personality as expected. Children also have certain values ​​in the family, society, nation and state. For example, (1) children are descendants; (2) children help their parents in their old age; (3) children help complete development work programs in villages or sub-districts; (4) children as leaders in the future. In reality, not all children experience or live life as expected. The fact that is seen in society, there are quite a number of children working in the informal sector. The place where these children do their work is often very dangerous and has a very bad impact on the child's future. The child will be an uneducated person. For example, it is very difficult for them to get a decent job, or it is difficult for them to adjust to the norms that apply in society. Furthermore, this will cause many other social problems in society. If they associate with a bad environment, these children can become criminals or the dregs of society.